Investigating the relationship between clinical competence and the incidence of needle-stick injuries (NSIs) and their contributing factors in nurses: a descriptive cross-sectional study in Southern Iran - Omid Zarei; Fatemeh Zeraatpishe; Najimeh Beygi; Maryam talebi moghadam; Seyede Fatemeh Mousavi Shahraki; Mohammad Mehdi Naghizadeh; Mostafa Bijani (BMC Nursing, 2025)
Abstract Background Needle-stick injuries (NSIs) pose a substantial occupational hazard, exposing healthcare professionals to potentially infectious diseases. Nurses’ clinical competence plays a crucial role in preventing and mitigating the incidence of NSIs. This study aimed to investigate the relationship between clinical competence and the incidence of NSIs, as well as the factors contributing to these injuries, among nurses in Fars Province, southern Iran, from March 2023 to May 2023. Methods This descriptive cross-sectional study included 264 nurses selected through convenience sampling. All participants were employed in various departments of teaching hospitals in Fasa city, southern Iran, during the study period. Data were collected using a demographic questionnaire and a clinical competence questionnaire specifically developed for nurses. The demographic questionnaire captured variables such as age, gender, marital status, educational background, departmental assignment, work experience, and weekly working hours. The clinical competence questionnaire consisted of 55 items assessing seven dimensions: clinical care, leadership, legal and ethical performance, professional development, interpersonal relationships, education and coaching, and critical thinking and research aptitude. Statistical analyses were performed using SPSS software (version 16), employing the Chi-square test, Kruskal-Wallis test, and multiple logistic regression analysis. A significance level of p < 0.05 was applied to all tests. Results The findings revealed that 39.4% of the participating nurses exhibited high clinical competence, 51.5% demonstrated moderate competence, and 9.1% were classified as having low competence. Statistical analysis indicated a significant association between clinical competence levels and needle-stick status (P = 0.002). Moreover, a significant difference was identified between clinical competence levels and the frequency of NSIs (P = 0.001). A logistic regression model was employed to assess the likelihood of NSIs based on demographic variables. The results showed that 178 participants (67.42%) had experienced needle-stick or sharp injuries within the preceding year. Among these, 63 males (35.3%) and 115 females (64.6%) reported such incidents. The highest incidence of needle-stick and sharp injuries occurred in the Operating Room (91.7%), followed by Dialysis (88.9%), Pediatrics (80%), Surgical Intensive Care (76.5%), Emergency (74.3%), Women’s Surgery (70%), Post-Cardiac Intensive Care (69.2%), Oncology (63.6%), Internal Medicine (59.1%), Surgery and Infectious Diseases (54.5%), Laboratory and Cardiac Intensive Care (52.9%), Men’s Surgery (50%), and the Psychiatric Ward (41.2%). Conclusions Considering that the majority of nurses working in hospitals exhibited moderate to low levels of clinical competence, it is recommended that hospitals implement an annual clinical competence assessment for nurses. Regular evaluations and targeted training programs can enhance nurses’ competence levels, thereby improving patient care quality and reducing the incidence of NSIs among healthcare providers. Additionally, specific strategies should be developed and implemented in medical centers and hospitals to mitigate the risk of NSIs across all hospital departments, particularly in high-risk areas such as operating rooms and dialysis units, where the prevalence of NSIs is significantly higher. Clinical trial number Not applicable.